1995
DOI: 10.1086/117470
|View full text |Cite
|
Sign up to set email alerts
|

Globular Clusters with Tidal Tails: Deep Two-Color Star Counts

Abstract: We examine the outer structure of 12 Galactic globular clusters using star-count analyses. Deep, two-color, photographic photometry is used to select and count stars with colors and magnitudes consistent with cluster-specific, color-magnitude sequences. The resulting reduction in the number of contaminating foreground stars allows us to push the star counts to significantly lower surface densities than has previously been possible. We find that most of our sample clusters show extra-tidal wings in their surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
292
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(316 citation statements)
references
References 21 publications
22
292
2
Order By: Relevance
“…Next, we adopt the method described by Grillmair et al (1995), which consists of selecting regions in the CMD where the "cluster vs. field contrast" is important. For this purpose, we use a so-called colour-magnitude S/N function s(i, j) defined by subdividing the CMD in multiple cells (50×50 bins here, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we adopt the method described by Grillmair et al (1995), which consists of selecting regions in the CMD where the "cluster vs. field contrast" is important. For this purpose, we use a so-called colour-magnitude S/N function s(i, j) defined by subdividing the CMD in multiple cells (50×50 bins here, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Terlevich (1987) and de la Fuente Marcos (1997 and references therein) performed realistic simulations of open cluster evolution. From the observational point of view, Grillmair et al (1995) and Leon et al (2000) detected important tidal tail extensions around galactic globular clusters using a wide-field star count analysis. Leon et al (1999) also found noticeable tidal tails around several binary star clusters in the Large Magellanic Cloud.…”
Section: Introductionmentioning
confidence: 99%
“…Recent N-body simulations of globular clusters embedded in a realistic galactic potential (Oh & Lin 1992;Johnston et al 1999) were performed in order to study the amount of mass loss for different kinds of orbits and different kinds of clusters, along with the dynamics and the mass segregation in tidal tails. Grillmair et al (1995) in an observational analysis of star counts in the outer parts of a few galactic globular clusters found extra-cluster overdensities that they associated partly with stars stripped into the Galaxy field.…”
Section: Tidal Truncationmentioning
confidence: 99%
“…For each field, a (B vs. B − V ) color-magnitude diagram was constructed, on which a field/cluster star selection was performed, following the method of Grillmair et al (1995), since cluster stars and field stars exhibit different colors. In this way present and past cluster members could be distinguished from the fore-and background field stars by identifying in the CMD the area occupied primarily by cluster stars.…”
Section: Tidal Tails From Wide-field Observationsmentioning
confidence: 99%
See 1 more Smart Citation